The impact of polls on the stock market : Empirical evidence from the bursa Malaysia / Awang Suffian Awang Shawal - Awang Shawal, Awang Suffian (2004)
Historically stocks tend to rally just before an election is announced. However prior research also suggests that there is no single discernable trend that allows one to predict with certainty the behaviour of the stock market during the election fervour. This paper looked at the impact of polls on the politically linked stocks on the main board of Bursa Malaysia in particular to identify whether the market trends following the most recent general election was similar to the trend following previous general elections in Malaysia.